Reconfiguration of static and dynamic thalamo-cortical network functional connectivity of epileptic children with generalized tonic-clonic seizures - Li, Yongxin; Wang, Jianping; Wang, Xiao; Chen, Qian; Qin, Bing; Chen, Jiaxu (Frontiers in Neuroscience, 2022)
Objective: A number of studies in adults and children with generalized tonic-clonic seizures (GTCS) have reported the alterations in morphometry, functional activity and functional connectivity (FC) in the thalamus. However, the neural mechanisms underlying the alterations of thalamus in patients with GTCS is not well understood, especially in children. The aim of the current study was to explore the temporal properties of functional pathways connecting thalamus in children with GTCS. Methods: Here, we recruited 24 children with GTCS and 36 age-matched healthy controls. Static and dynamic FC approaches were used to evaluate alterations in the temporal variability of thalamo-cortical networks in children with GTCS. Dynamic effective connectivity (dEC) method was also used to evaluate the directions of the fluctuations in effective connectivity. In addition, the relationships between the dynamic properties and clinical features were assessed. Results: The static FC analysis presented significantly decreased connectivity patterns between bilateral thalamus and between the thalamus and right inferior temporal gyrus. The dynamic connectivity analysis found decreased FC variability in the thalamo-cortical network of epilepsy children. Dynamic EC analyses identified increased connectivity variability from the frontal gyrus to the bilateral thalamus and decreased connectivity variability from right thalamus to left thalamus and from right thalamus to right superior parietal lobe. In addition, correlation analysis revealed that both static FC and connectivity temporal variability in the thalamo-cortical network related to the clinical features (epilepsy duration and epilepsy onset time). Significant: Our findings of both increased and decreased connectivity variability in the thalamo-cortical network imply a dynamic restructuring of the functional pathways connecting thalamus in children with GTCS. These alterations of static and temporal dynamic pathways connecting the bilateral thalamus may extend our understanding of the neural mechanism underlying the GTCS in children.